Effect of geometric characteristics of helical piles on the lateral displacement in sandy slopes by loading surcharge - Mir abas Bahri; Mahyar Arabani (Results in Engineering)
Helical piles are a group of deep foundations with a good bearing capacity against axial and lateral forces. Despite extensive research on the performance on flat ground, fewer studies have been conducted on the performance of helical piles on slopes. Hence, in the present research, the lateral displacement of helical piles on the sloping ground by loading surcharge was investigated. For this purpose, 1g laboratory test models of a reinforced sand slope were constructed with a series of cylindrical and helical piles with different pitches and diameters as well as numerical simulations. PLAXIS 3D software was used along with the finite element method and the hardening soil model to assess the effects of geometric characteristics of helical piles on lateral displacement in a sandy slope. According to the laboratory results, the vertical load on sandy slopes was up to 44 % higher than that of cylindrical piles with the same shaft diameter. Laboratory results also reveal that the vertical load increases by 34, 20, and 12 %, respectively by increasing the helix depth, decreasing the helix pitch, and installing the piles in a slanted manner. Furthermore, considering the results of verification through numerical analysis, the vertical load on the slope crest when reinforced with helical piles was up to 47 % higher than when reinforced with cylindrical piles with the same shaft diameter. In numerical analysis, the vertical load on the slope crest increased by 37, 25, and 15 %, respectively with increasing helix depth, decreasing helix pitch, and inclined installation of piles. Overall, the findings of this study revealed that helical piles exhibited superior performance compared to cylindrical piles, making them a suitable alternative for practical deployment.